2000
DOI: 10.1002/1097-0177(2000)9999:9999<::aid-dvdy1062>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Associations of FGF-3 and FGF-10 with signaling networks regulating tooth morphogenesis

Abstract: The morphogenesis and cell differentiation in developing teeth is governed by interactions between the oral epithelium and neural crest‐derived ectomesenchyme. The fibroblast growth factors FGF‐4, ‐8, and ‐9 have been implicated as epithelial signals regulating mesenchymal gene expression and cell proliferation during tooth initiation and later during epithelial folding morphogenesis and the establishment of tooth shape. To further evaluate the roles of FGFs in tooth development, we analyzed the roles of FGF‐3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
218
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(228 citation statements)
references
References 79 publications
5
218
0
5
Order By: Relevance
“…This thickened epithelium signals back to the underlying mesenchyme to direct growth and patterning. We have previously shown that in both limbs and teeth, Fgf10/Fgfr2b signaling plays important roles in initial budding and in maintaining growth (24,26). Here we provide evidence that Fgf10 signals from the palatal mesenchyme to its receptor in the palatal epithelium and that signals pass back to the mesenchyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This thickened epithelium signals back to the underlying mesenchyme to direct growth and patterning. We have previously shown that in both limbs and teeth, Fgf10/Fgfr2b signaling plays important roles in initial budding and in maintaining growth (24,26). Here we provide evidence that Fgf10 signals from the palatal mesenchyme to its receptor in the palatal epithelium and that signals pass back to the mesenchyme.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of Fgfr2b, Fgf3, Fgf7, Fgf10, Ptc1, and Shh 35 S-UTP-labeled riboprobes, in situ hybridization, and image analysis have all been described previously (5,26,(48)(49)(50). Antisense Smo probe (a kind gift from M.T.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…Furthermore, Wnt signaling was shown to be required in the molar mesenchyme for the bud to cap stage transition and primary enamel knot formation (Chen et al 2009). The signals induced in the mesenchyme by epithelial Fgfs and acting reciprocally to the epithelium include Activin, Fgf3, and Fgf10 (Ferguson et al 1998;Kettunen et al 2000). These signals regulate the subsequent epithelial morphogenesis and the enamel knot formation (Fig.…”
Section: Signaling Network Regulating Tooth Developmentmentioning
confidence: 99%
“…34,35 Importantly, there is also evidence that signalling from Fgf3 and Fgf10 in mesenchyme of the tooth bud is also required for Shh expression in the primary enamel knot epithelium. 36,37 Sprouty (Spry) genes encode a small group of intracellular FGF antagonists which are produced in response to FGF signalling and therefore modulate transduction in target cells. 38 Among these genes, Spry2 and Spry4 are expressed in epithelium and mesenchyme of the developing tooth, respectively, and a loss-offunction associated with either gene results in the formation of extra teeth within the diastema region of the mouse dentition, predominantly affecting the mandible.…”
Section: Fibroblast Growth Factor Signallingmentioning
confidence: 99%